Antimicrobial and Phytochemical Activity of Coconut Shell Extracts - Gebila Mazaya; Karseno Karseno; Tri Yanto (Turkish Journal of Agriculture: Food Science and Technology)
Coconut shell extract contains phytochemical compounds tannins, saponins and steroids which are thought to act as antimicrobial compounds. This makes coconut shell extract has great potential as a natural preservative, one of which is the natural preservative coconut sap. This study aims to know the effect of coconut shell type, extraction time, extraction temperature and the combination of the three treatments on the antimicrobial activity and phytochemical extracts produced. This study using a Randomized Block Design (RBD). The factors tested were coconut shell type consisting of: fresh old coconut shell; dry old coconut shell; fresh young coconut shell; dry young coconut shell; length of extraction time consisting of: 3 and 5 hours’ extraction time, and extraction temperature consisting of: 28°C and 70°C. The variables observed in this study include microbiological and phytochemical variables. The results showed that all type of coconut shell extract contains phytochemical compounds such as tannin, saponins, and some samples contain steroid compounds and had the ability of antimicrobial activity, especially in the bacterium A.aceti. The combination of a dry old shell with an extraction time of 3 hours and extraction temperature of 28°C has the highest antimicrobial activity against A.aceti bacteria with inhibition zone diameter of 13.25 mm, positive containing phytochemical compounds tannins, saponins and steroids and contains total phenol levels of 18.67 mg/100g.